ALLERGIC CONTACT DERMATITIS AND ASSOCIATED ALLERGIC DERMATOSES - Qobiljonova Shaxnoza Rustam qizi; Malikov Samandar Gafurdjanovich; Mirzayev Mustafo Murodiljon o'gli (Web of Journals Publishing, 2025)
Allergic (sensitization or eczema-like) contact dermatitis is one of the most common diseases in dermatological practice, and, according to various sources, is observed in 2-2.5% of the world's population [9, 21, 25]. In turn, allergic dermatoses are a generalized group of dermatoses, in the genesis of which immunological reactions occur in the skin in response to the effects of exogenous and endogenous factors play a role. The group of allergic dermatoses includes eczema, AD, ACD, characterized by a chronic course, frequent relapses, requiring long-term treatment and rehabilitation [6,8,13]. The study of the etiology and pathogenesis of allergic dermatoses, as well as the improvement of therapy methods remains one of the most pressing problems of modern dermatology.